PERAN SERTA MAHASISWA DALAM MENINGKATKAN AKUNTABILITAS LAPORAN KEUANGAN KOPERASI GUNUNG LUHUR BERKAH SUBANG - Trisandi Eka Putri; Icih Icih; Dede Entis; Elsa Auliya Agustien; Putri Ayu (STIESA-PRESS, 2023)
One of the problems of cooperatives in Indonesia is the existence of supervision that has not run optimally so that strong, healthy, independent, tough and competitive cooperatives in accordance with the identity of cooperatives cannot be realized. Cooperative supervision is related to accountability, especially financial reports. To increase the accountability of the cooperative's financial statements, it is necessary to audit the financial statements by a public accountant. Based on this, assistance in the preparation of financial statement audits is needed because the GLB Cooperative has never been audited by a public accountant. The parties involved in this assistance consist of the Chairperson, Secretary, Accounting and Finance Division Employees and other necessary sections. This community service is carried out using the method of socialization, consultation and observation by lecturers and students of STIE Sutaatmadja Subang. The socialization of real sector accounting guidelines and auditing of financial statements has been well conveyed. Consultations related to the issue of conformity of the GLB Cooperative's financial statements with accounting guidelines have been discussed. Consultations related to audits have been well conveyed. Field observations to determine the cooperative's business processes in order to determine the right accounting guidelines have also been carried out properly. At the time this report was prepared, the 2021 GLB Cooperative Financial Statements were being audited by KAP Sabar.